Degradação fotoeletroquímica de corantes dispersos em efluente têxtil utilizando fotoanodos de Ti/TiO2 - Brunelli, Tamara F. T. [UNESP]; Guaraldo, Thaís T. [UNESP]; Paschoal, Fabiana M. M. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Sociedade Brasileira de Química, 2009)
The degradation of disperses dyes in aqueous solution and in effluents from textile industry has been investigated by photoelectrocatalytic oxidation using nanoporous thin films electrodes of Ti/TiO2. Samples of dispersil black dye and dispersil blue dye after 300 min of photoelectrolyzed at applied potential of +1.0 V and UV irradiation exhibited 100% of discoloration and 90% and 64% reduction total organic carbon, respectively. The proposed method was applied with success in a textile industry effluent containing residues of these dyes, which after 300 min of treatment leads to reduction of 60% of COD and 64% removal of TOC.
Photoeletrochemical degradation of disperse dyes in textile effluent on photoanodes of Ti/TiO2
Keywords: disperse dye; textile effluent; photoeletrochemistry